The Symbolic Feelings of Opposites: An Analysis of the Characters in Bai Xianyong's Taipei People - Cheng Zhuo (SHS Web of Conferences)
Critical analysis of the stylistic features in the works of Bai Xianyong has already been richly explored by previous scholars. The theories on temporal and spatial themes have gradually made the analysis of artistic techniques a tool for supporting arguments. However, as the fundamental means of style formation, analysing artistic techniques alone remains an effective way to understand the article and the author's writing style and purpose. This article analyses the character-shaping techniques in Bai Xianyong's Taipei People, especially the use of metaphor and symbolism in presenting oppositions. Through in-depth analysis of The Eternal Snow Beauty and Wandering in the Garden, Waking from a Dream, it reveals how Bai Xianyong uses techniques such as symbolism and metaphor to reflect the oppositional relationships between historical changes, social realities, and individual destinies. These artistic techniques not only shape the complex characters but also express the author's deep thoughts on history and reality and his emotional attitude toward the social group that migrated to Taipei. Therefore, while Bai Xianyong integrates unique writing techniques from both Chinese and Western literature, he uses symbolism to soften oppositions, resulting in a unified texture in his works where conflicts are apparent but not contradictory.